2022
DOI: 10.1128/jvi.00944-22
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever Virus pI215L Inhibits Type I Interferon Signaling by Targeting Interferon Regulatory Factor 9 for Autophagic Degradation

Abstract: African swine fever virus (ASFV) causes a highly contagious and lethal disease in pigs and wild boars that is currently present in many countries, severely affecting the global pig industry. Despite extensive research, effective vaccines and antiviral strategies are still lacking, and many fundamental questions regarding the molecular mechanisms underlying host innate immunity escape remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 74 publications
1
18
0
Order By: Relevance
“…Ectopic expression of pI215L inhibits ISRE promoter activity and mRNA induction of the IFN-I-stimulated genes ISG15 and IFIT1 upon IFN-I stimulation, being this inhibition pI215L-dose-dependent and strictly relies on the E2 activity. In line with this, a recently published paper by Li et al (2022) showed that pI215L inhibited IFN-I signaling by degrading IRF9, implying the I215L protein as a modulator of the JAK/STAT pathway. However, the intrinsic pI215L E2-ubiquitin-conjugating function was not shown to be involved in the inhibition of the IFN-I pathway.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Ectopic expression of pI215L inhibits ISRE promoter activity and mRNA induction of the IFN-I-stimulated genes ISG15 and IFIT1 upon IFN-I stimulation, being this inhibition pI215L-dose-dependent and strictly relies on the E2 activity. In line with this, a recently published paper by Li et al (2022) showed that pI215L inhibited IFN-I signaling by degrading IRF9, implying the I215L protein as a modulator of the JAK/STAT pathway. However, the intrinsic pI215L E2-ubiquitin-conjugating function was not shown to be involved in the inhibition of the IFN-I pathway.…”
Section: Discussionsupporting
confidence: 56%
“…pI215L has been implicated in the modulation of the innate immune response by preventing IFN-I production through inhibition of NF-κB and AP1 (Barrado-Gil et al, 2021) and by regulating the cGAS-STING pathway through the inhibition of TBK1 phosphorylation (Huang et al, 2021). Recently, it has been described that I215L modulates IFN-I signaling through degradation of IRF9 via the autophagosomal/lysosomal pathway (Li et al, 2022). However, no studies involving ubiquitin-conjugating activity of pI215L as a negative regulator of the IFN-I production or IFN-I signaling have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the V protein of Newcastle disease virus inhibited IFN signaling by promoting ubiquitination-dependent degradation of MAVS via RNF5 [34]. African swine fever virus pI215L protein recruited RNF138 to reduce K63-linked ubiquitination of TBK1, resulting in the inhibition of IFN production [35]. The NNV CP is responsible for host innate immune evasion, however its exact evasion mechanisms are not well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…ASFV pI215L (UBCv1) can interfere with the formation of ISG3 in both ubiquitin-conjugating enzyme-activity-independent and dependent manners. ASFV pI215L (UBCv1) can interact with IRF9 and mediate the degradation of IRF9 via autophagy-lysosome pathway, which is independent of its ubiquitin-conjugating enzyme activity [ 85 ]. Additionally, ASFV pI215L (UBCv1) can also mediate the degradation of STAT2 via ubiquitin-proteasome pathway, which is dependent on its ubiquitin-conjugating enzyme activity [ 86 ].…”
Section: Suppression Of Ifn-i Production and Ifn-induced Antiviral Re...mentioning
confidence: 99%